EVALUATION OF DIFFERENT GRADES OF GUAR GUM, ACACIA GUM, AND POLYVINYL PYRROLIDONE AS CROSS-LINKERS IN PRODUCING SUBMICRON PARTICLES - ELSAYED YAGOUB, NEGLA ABDULGHANI; MOHAMED NUR, ABUBAKAR OSMAN; ALEANIZY, FADILAH SFOUQ; OSMAN, ZUHEIR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The main goal of this research is to evaluate using of guar gum (GG), Arabic gum, and poly-vinylpyrrolidone, each of two viscosity grades, as crosslinking agents in producing nanoparticles and submicron particles. Methods: The method used is the preparation of nanoparticles of carbamazepine using two viscosity grades of polymers (GG, acacia gum, and polyvinyl pyrrolidine) by emulsification/solvent evaporation technique. Based on a statistical design composed of mixed 32-levels factors and 13-levels factor was selected for screening and preliminary optimization purposes. The collected nanoparticles from the first portion of all 24 runs were subjected to the following qualifications, particle diameter, polydispersity index (PDI%), zeta potential, entrapment efficiency (EE%), and drug loading. Results: The study revealed that based on the obtained findings and the associated statistical analysis, influences of stirring rate, polymer type, polymer grade, and polymer loading in different formulation runs resulted in produced particles with different characteristics such as particle size of different formulation series are in sub-micron (0.13–91.83 μm) with EE% (max 52.28%), reduced EE observed in this study can be attributed to lower polymer load in the dispersed phase (1% and 10%) and zeta potential values were small (range 35.69–41.68), all preparation factors have no significant effect on zeta potential, PDI values (close to zero) showed that all the samples formed monodispersions in water and its due to steric hindrance than a surface charge. Conclusion: The study recommends that different polymers need special techniques for producing cross-linked particles with sub-micron particles, no universal technique can be applied. Keywords: Polymer, Guar gum, Acacia gum, Polyvinyl pyrrolidine, Carbamazepine, Emulsification/solvent evaporation technique, Stirring rate.